2020
DOI: 10.3389/fmicb.2020.01558
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Organelles Reorganization During Zika Virus Infection of Human Cells

Abstract: Zika virus (ZIKV) is an enveloped positive stranded RNA virus belonging to the genus Flavivirus in the family Flaviviridae that emerged in recent decades causing pandemic outbreaks of human infections occasionally associated with severe neurological disorders in adults and newborns. The intracellular steps of flavivirus multiplication are associated to cellular membranes and their bound organelles leading to an extensive host cell reorganization. Importantly, the association of organelle dysfunction with disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
(91 reference statements)
1
24
2
1
Order By: Relevance
“…Similarly, the NS4A and NS4B proteins of ZIKV have also been found to induce lipophagy and thereby inhibit neurogenesis in human embryonic neural stem cells. The occurrence of ZIKV-induced lipophagy was similarly demonstrated in a recent study on the reorganization of organelles upon ZIKV virus infection of different cell lines, which found that the number and volume of LDs were reduced in ZIKV-infected cells, and this virus might induce LDs biogenesis, which stimulate the initial viral replication, and then trigger lipophagy to reduce LDs and release FFAs from these lipid structures (García et al, 2020). Meanwhile, the Japanese encephalitis virus (JEV) infection, analogous to other flaviviruses (DENV, WNV and ZIKV), decreased the number of LDs per cell indicating a link between lipid metabolism and virus replication (Sarkar et al, 2020).…”
Section: Represented By Denvsupporting
confidence: 57%
“…Similarly, the NS4A and NS4B proteins of ZIKV have also been found to induce lipophagy and thereby inhibit neurogenesis in human embryonic neural stem cells. The occurrence of ZIKV-induced lipophagy was similarly demonstrated in a recent study on the reorganization of organelles upon ZIKV virus infection of different cell lines, which found that the number and volume of LDs were reduced in ZIKV-infected cells, and this virus might induce LDs biogenesis, which stimulate the initial viral replication, and then trigger lipophagy to reduce LDs and release FFAs from these lipid structures (García et al, 2020). Meanwhile, the Japanese encephalitis virus (JEV) infection, analogous to other flaviviruses (DENV, WNV and ZIKV), decreased the number of LDs per cell indicating a link between lipid metabolism and virus replication (Sarkar et al, 2020).…”
Section: Represented By Denvsupporting
confidence: 57%
“…To explore the antiviral activity of RES against ZIKV in a retinal cell model, we employed ARPE-19, which is a spontaneously arising RPE cell line of male origin that retains normal karyology and hTERT-RPE-1 (from now on, abbreviated hRPE-1), which is a near-diploid human cell line of female origin. Both cell lines maintain the morphology and functions of in vivo human RPE cells [2,16].…”
Section: Effect Of Res On Zikv-infected Rpe Cell Linesmentioning
confidence: 97%
“…Then, cells were fixed with 10% formaldehyde for 10 min, washed and stained with 0.1% crystal violet in 20% ethanol. Plaques were counted, and viral yield determined [16].…”
Section: Viral Yield Determinationmentioning
confidence: 99%
“…Notably, SUMOylation of ZIKV NS5 is SIM-independent [ 32 ]. In NPCs, on the contrary, nuclear localization of NS5 resulted in a significant reduction in the number of PML NBs [ 33 ].…”
Section: Positive Sense Single Stranded Rna Virusesmentioning
confidence: 99%